Aspects of Arabic Influence on Astronomical Tables in Medieval Europe - Chabás, José (Suhayl. Journal for the History of the Exact and Natural Sciences in Islamic Civilisation, 2015)
Transmission in Medieval Europe of astronomical tables and their accompanying texts, originally written in Arabic, has a complex history and it involves various mechanisms, which include translation, revision, adaptation, appropriation, copying, and commentaries. This paper reviews such features and presents examples of them.